Reliability and validity of adapted gravitational goniometer and hand-held inclinometer in measuring shoulder mobility - Mongkol, Sarayoot; Poomsutat, Pakavalee; Saunpiayoong, Ratnaporn (Journal of Associated Medical Sciences, 2017)
Background: Goniometer is a physical therapy tool for evaluation of the range of motion. Standard goniometer is commonly used in clinical practice. However, simple and inexpensive tools are necessary for community based practice. Objectives: To study reliability and validity between adapted gravitational goniometer (AGG) and hand-held inclinometer (HHI) in measuring shoulder range of motion. Materials and methods: One hundred and eight female subjects aged between 18-22 years old (19.25±0.99 years old) without shoulder operation or injuries of shoulder, clavicle, scapular, and shoulder muscle recruited for this study. All subjects were evaluated for the ranges of motion of shoulder flexion, extension, abduction, and adduction by AGG and HHI. Results: Mean average of shoulder flexion measured by AGG (167.69±6.3 degrees) and by HHI (167.78±7.23 degrees) was significant correlated at r=0.84 (p<0.05). Mean average of shoulder extension measured by AGG (36.29±10.84 degrees) and by HHI (35.19±11.14 degrees) was significant correlated at r=0.67 (p<0.05). Mean average of shoulder abduction measured by AGG (169.44±7.28 degrees) and by HHI (168.48±7.66 degrees) was significant correlated at r=0.78 (p<0.05). Mean average of shoulder adduction measured by AGG (49.05±7.89 degrees) and by HHI (48.08±8.35 degrees) was significant correlated at r=0.66 (p<0.05). The validity study of AGG and HHI revealed by having no significant differences of average ranges of shoulder flexion, shoulder extension, shoulder abduction, and shoulder adduction (p>0.05) measured by two devices. Conclusion: Adapted gravitational goniometer is reliable and valid in comparison to hand-held inclinometer for evaluation of shoulder flexion, shoulder extension, shoulder adduction, and shoulder abduction.